PROYEKSI PRODUKSI DAN PERMINTAAN JAGUNG, PAKAN DAN DAGING AYAM RAS DI INDONESIA (Projections of Maize, Feed and Chicken Meat Production and Demand in Indonesia) - KARIYASA, KETUT; M. SINAGA, BONAR; ADNYANA, M.O. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004)
Assessment on “Projections of Maize, Feed and Chicken Meat Production and Demand in Indonesia is focused to analyze a balance between the domestic production and demand for the next ten years, as well as to analyze its level response to influence factors.This research used the national time series data for 1980 to 2001 period. The econometric model (simultaneous regression) approach through the two stage least squares (2SLS) method had been implemented in order to reach the objectives of this research. The projection results shown that on technology level and policies unchanged, the domestic production from those commodities until 2010 year are predicted not sufficient to meet its demand, so that targeting for the maize and chicken meat self-sufficient in 2005 can not be reach. It is better, if effort to increase of the corn domestic production is more prioritized on improvement of the technology aspect, because corn productivity is more response to this aspect than to the other ones. The feed production and demand that were more response to the maize price than to the feed price, and also the chicken meat production and demand that were more response to the chicken meat price itself than the feed price proofed that the feed market structure in Indonesia tend is close to oligopoly market structure.
Keywords: Projection, Self-Sufficient, Elasticity, Maize, Feed, Chicken Meat